Rekomendasi Kelayakan Peminjam menggunakan Metode Fuzzy Tsukamoto - Muh Hamim Fajar; Edy Santoso; Lailil Muflikhah (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Cooperatives is one of the business fields that offer savings and loans. To become a member of the cooperative or to make savings and loans a person must meet the requirements that have been determined by the cooperative. Due to the limited funds owned by the cooperative, the selection of someone to get help is done to reduce payment problems. In this study, calculations were carried out in order to recommend the feasibility of the borrower using the fuzzy tsukamoto method approach. There are several processes using the Fuzzy Tsukamoto method to solve these problems is Fuzzyfication, Tsukamoto's Fuzzy Inference system and defuzzification. In the process of fuzzyfication is to change the real variables into fuzzy variables. Then, the process of the tsukamoto fuzzy inference system is to find the value of -predicate and z, and finally defuzzification is to change the fuzzy variable into a real variable. Based on results of the tests carried out use the Tsukamoto fuzzy method of cooperative data KUD "SRI LESTARI" obtained very good performance results with an accuracy value of 87.88% and an F-1 score of 92.96%.